Assessing minority ethnic’s perception towards aging process and physical exercise in Sabah, Malaysia / Lizinis Cassendra Frederick Dony ... [et al.] - Frederick Dony, Lizinis Cassendra; Ismail, Sarimah; Rosline, Abdul Kadir; Muhamad, Reziana; Mojiol, Andy (2019)
The aim of this study is to highlight on why aging and physical exercise are essential for the improvement of sustainability healthcare and sportsmanship integration policy in Sabah. It also focuses on sustainable human capital development inclusive recreational, occupational, safety and healthy concern among the governments, schools, the food industry and the social media communication. To delay aging and enhance more physical exercise as part of healthy life development strategies seen as strengths and opportunity strategies. Grounded theory methodology was used for this study which assess the thirty respondents through simulation 0.4KM running activities. Whereas, the individually group is randomly face to face interviewed. Result of this study shows that public health approaches are highly contributing to unsolved 60% health risks and in economic inequalities. Therefore, to address this problem, a sustainability of health care education needs to focus on aging prevention by giving a primary concern among the minority ethnic who is acknowledged as community in need, female, athletes who has been injured and facing career transition. Finally, organization should increase CSR on healthy life setting as well to provide future quality human capital development in Sabah and Malaysian in general.